Thrombospondin-2 promotes prostate cancer bone metastasis by the up-regulation of matrix metalloproteinase-2 through down-regulating miR-376c expression - Po-Chun Chen (Journal of Hematology & Oncology, 2017)
Abstract Background Thrombospondin-2 (TSP-2) is a secreted matricellular glycoprotein that is found to mediate cell-to-extracellular matrix attachment and participates in many physiological and pathological processes. The expression profile of TSP-2 on tumors is controversial, and it up-regulates in some cancers, whereas it down-regulates in others, suggesting that the functional role of TSP-2 on tumors is still uncertain. Methods The expression of TSP-2 on prostate cancer progression was determined in the tissue array by the immunohistochemistry. The molecular mechanism of TSP-2 on prostate cancer (PCa) metastasis was investigated through pharmaceutical inhibitors, siRNAs, and miRNAs analyses. The role of TSP-2 on PCa metastasis in vivo was verified through xenograft in vivo imaging system. Results Based on the gene expression omnibus database and immunohistochemistry, we found that TSP-2 increased with the progression of PCa, especially in metastatic PCa and is correlated with the matrix metalloproteinase-2 (MMP-2) expression. Additionally, through binding to CD36 and integrin ανβ3, TSP-2 increased cell migration and MMP-2 expression. With inhibition of p38, ERK, and JNK, the TSP-2-induced cell migration and MMP-2 expression were abolished, indicating that the TSP-2’s effect on PCa is MAPK dependent. Moreover, the microRNA-376c (miR-376c) was significantly decreased by the TSP-2 treatment. Furthermore, the TSP-2-induced MMP-2 expression and the subsequent cell motility were suppressed upon miR-376c mimic stimulation. On the other hand, the animal studies revealed that the bone metastasis was abolished when TSP-2 was stably knocked down in PCa cells. Conclusions Taken together, our results indicate that TSP-2 enhances the migration of PCa cells by increasing MMP-2 expression through down-regulation of miR-376c expression. Therefore, TSP-2 may represent a promising new target for treating PCa.